Market Efficiency and the Post-Earnings Announcement Drift* - Chung, Dennis Y.; Hrazdil, Karel (Contemporary Accounting Research, 2011)
We examine whether the post-earnings announcement drift (PEAD) varies cross-sectionally with short-horizon return predictability from order flows, which characterizes the information environment and reflects the extent to which information is efficiently impounded in prices. We first demonstrate that this proxy for market efficiency (developed by Chordia, Roll, and Subrahmanyam 2008) captures the degree of market frictions that limit arbitrage activities. We then present evidence that the inverse of short-horizon return predictability is negatively associated with the PEAD and remains statistically and economically significant after controlling for a wide range of explanatory variables used in prior research. Finally, although we find that profits of implementing the PEAD trading strategy are significantly reduced by transaction costs, we demonstrate that profits continue to remain statistically and economically significant for the less efficient firms that face otherwise higher barriers to arbitrage. Our results indicate that short-horizon return predictability from order flows better explains stock returns after earnings announcements.